Antarctic data impact experiments with Polar WRF during the YOPP‐SH summer special observing period. (2nd June 2022) - Bromwich, David H.; Powers, Jordan G.; Manning, Kevin W.; Zou, Xun
Abstract: Data impact experiments are conducted employing the Polar Weather Research and Forecasting (WRF) model during the YOPP‐SH summer special observing period (SOP) using the Antarctic Mesoscale Prediction System (AMPS) framework to determine the forecast impact of numerous additional radiosondes collected during the SOP. Hybrid variational‐ensemble three‐dimensional data assimilation is performed on model forecast domains over Antarctica and the Southern Ocean using all regular observations normally available (Experiment "NoSOP") and using the same set plus the extra soundings launched for the SOP (Experiment "SOP"). The SOP results show better near‐surface temperature and wind‐speed forecasts than the NoSOP results, primarily over West Antarctica. Radiosonde profiles confirm that temperature and wind‐speed forecasts are improved throughout the troposphere with the addition of the SOP radiosonde data, but the results for relative humidity are variable. Temperatures are improved at lower levels early in the forecasts, whereas wind speeds are better at higher levels later in the forecasts. An evaluation against the ERA5 global reanalysis that provides a much broader perspective reveals that the improved forecast skill for the SOP experiment persists up to 72 hours for temperature, wind speed, and relative humidity. The gains, however, are primarily confined to the Antarctic continent, consistent with the additional radiosonde spatial coverage being mainly poleward of 60°S. With extra radiosondes concentrated over the Antarctic Peninsula, SOP forecasts of the region downstream of the Peninsula were significantly improved compared to NoSOP forecasts. In addition, it is found that the assimilation of the additional radiosonde data can have a greater impact on the forecasts of strong cyclones, as shown for a major coastal cyclone affecting West Antarctica, with improvements in its magnitude and track. The results also suggest that increasing radiosonde launches at lower southern latitudes would improve forecasts over the Southern Ocean, especially during austral winter. Abstract : During the Antarctic summer season, 2, 244 additional radiosondes were launched from 24 land‐based stations and five ships (top). Following assimilation of these observations into Polar Weather Research and Forecasting (WRF) model, temperature predictions were improved at lower‐tropospheric levels early in the forecasts, whereas wind‐speed predictions were improved at higher levels later in the forecasts, with this occurring mainly south of 60°S (bottom). To improve Antarctic winter prediction, the results suggest that additional radiosonde data from lower latitudes would better capture the atmospheric state.